PENGARUH E-SERVQUAL TERHADAP E-TRUST YANG DIMEDIASI OLEH E-SATISFACTION DAN DIMODERASI OLEH PROMOSI PADA MAHASISWA PENGGUNA GRABFOOD FAKULTAS EKONOMI DAN BISNIS UNIVERISTAS HALU OLEO - Yolandha De Ventura Keytimu; Alida Palilati; Yusuf (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to examine and analyze the effect of E-Service Quality on E-Trust, with E-Satisfaction as the mediating variable and Promotion as the moderating variable, among GrabFood users who are students The population in this study consists of 105 who use the GrabFood service. The sampling technique employed the purposive sampling method. Data analysis in this study utilized by the Smart PLS program version 4.0.9.8 The results of the study indicate that (1) E-Servqual has a positive and significant effect on E-Satisfaction. (2) E-Servqual was also found to have a positive and significant effect on E-Trust. (3) E-Satisfaction has a positive and significant effect on E-Trust. (4) E-Satisfaction was found to act as a mediating variable in the relationship between E-Servqual and E-Trust. (5) Promotion, as a moderating variable, does not have a significant effect on the relationship between E-Servqual and E-Trust, and (6) Promotion was found to have a significant effect as a moderating variable in the relationship between E-Servqual and E-Satisfaction, with a negative direction of the relationship.